In silico and molecular docking analysis of the flavones present in colocasia esculenta (L.) schott with the 1tsr p53 Protein - Tacderas, Mary Teresa Beatrice B. (Animo Repository, 2022)
We performed in silico study of flavones – p53 protein interaction by analyzing the molecular docking mechanism between four types of flavones, Apigenin, Chrysoeriol, Diosmetin, and Luteolin present in Colocasia esculenta (L.) Schott - (Taro) with the 1tsr p53 protein to determine which of the four flavones would exhibit good binding affinity, stability and interaction. Previous studies has shown that p53 protein behaves like as a tumor suppressor that triggers the apoptosis process in the cell which disrupts any tumor progression and proliferation. Phytochemicals such as flavonoids have played a role in cancer cell signaling and in the prevention of genotoxic compounds. Lipinski’s Rule of five and ADMET analysis were used as criteria for the initial screening of the flavones in the druglikeness evaluation which all four types of flavones passed. Molecular docking analysis using Autodock Vina revealed Diosmetin and Apigenin to have the strongest binding affinity (-5.1 kcal/mol) among the flavones, but slightly weaker than the positive control COTI-2 (-5.3 kcal/mol). Most of the binding sites of these four flavones protein ligand onto the 1tsr p53 protein receptor were clearly located through the Ramachandran contour maps. It was also worth noticing that both Diosmetin and Apigenin has the same binding types (e.g. conventional hydrogen bonds, pi-alkyl, and pi-pi interactions) with the 1tsr p53 protein compared to the other two flavones. Statistically, all four flavones showed no significant difference with the unbound protein and bound protein ligands with the 1tsr p53 protein receptor for the following p-values: p = 0.755 for Apigenin, p = 0.800 for Chrysoeriol, p = 0.686 for Diosmetin, and p = 0.555 for Luteolin. Further analysis using CABS-flex suggested that all four types can stably bind to the 1tsr p53 protein with no significant changes in structure based on the fluctuation plot and the superimposed models of unbound and bound p53. Overall, the in silico study showed that all four flavones are potential drug candidates that can regulate the protein’s signaling pathways in activating apoptosis but among the four flavones, Diosmetin and Apigenin demonstrated the strongest contender as tumor suppressor next to COTI-2 molecule.